Analisis Pengalaman Wisatawan pada Ruang Publik Pariwisata di Batu Cave Malaysia - Ahmad Syukron Syahbana; Lady Khania Cahya R. S; Laudza Ahmad Zaki; Maulana Hasan As’ariy; Tri Wulan Setiawati; Eva Azkiyatur Rifi’iyah; Ridwan Robbani (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the influence of cleanliness, supporting facilities, and accessibility on tourists’ experience and satisfaction in the tourism public space of Batu Caves, Malaysia. A quantitative method was employed, distributing questionnaires to 73 tourists. The research instrument used a Likert scale, which was validated and tested for reliability before being analyzed descriptively. The findings show that all three variables received high average scores ranging from 3.90 to 4.16, suggesting that tourists perceive the cleanliness, supporting facilities, and accessibility of Batu Caves to be in good condition. Cleanliness and accessibility received the highest evaluations, while supporting facilities were also considered adequate. These factors collectively contributed to high levels of tourist experience and satisfaction, which ranged from 4.04 to 4.15. The study concludes that the quality of public space plays a significant role in shaping tourist satisfaction. Proper management of cleanliness, amenities, and accessibility helps create a positive environment that enhances the overall tourist experience.